2018
DOI: 10.1002/jcp.27053
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human mitogen‐activated protein kinase 15 (extracellular signal‐regulated kinase 7/8) and its functions: A recent update

Abstract: Mitogen-activated protein kinase 15 (MAPK15), originally also known as extracellular signal-regulated kinase 7/8, is the most recently identified atypical MAPK and the least studied so far. Examinations of the role of MAPK15 in various cell lines and model systems indicate that MAPK15 participates in a variety of cellular activities such as promoting cell proliferation, cell transformation, and apoptosis; stimulating autophagy; regulating cell division, ciliogenesis, and protein secretion; and maintaining geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…The ERK pathway comprises several proteins that belongs to the family of mitogen-activated protein kinases (MAPK). These regulate diverse physiological and cellular processes, such as gene expression, cell division, survival, apoptosis, differentiation, and motility [15,16]. In metastatic processes, the MAPKs regulate EMT, invasion, angiogenesis, and resistance to therapy [7].…”
Section: Extracellular-signal Regulated Kinase: Structure and Funcmentioning
confidence: 99%
See 2 more Smart Citations
“…The ERK pathway comprises several proteins that belongs to the family of mitogen-activated protein kinases (MAPK). These regulate diverse physiological and cellular processes, such as gene expression, cell division, survival, apoptosis, differentiation, and motility [15,16]. In metastatic processes, the MAPKs regulate EMT, invasion, angiogenesis, and resistance to therapy [7].…”
Section: Extracellular-signal Regulated Kinase: Structure and Funcmentioning
confidence: 99%
“…Within the conventional MAPKs, the following subfamilies are categorized: ERKs, c-Jun N-terminal kinases/stress-activated protein kinases (JNKs/SAPKs) and p38, and ERK1/2 and ERK5. ERK3/4 and ERK7/8 are atypical MAPKs [15,17]. Several members of the ERK subfamily participate in regulation of growth, differentiation, survival, and cell motility [18].…”
Section: Extracellular-signal Regulated Kinase: Structure and Funcmentioning
confidence: 99%
See 1 more Smart Citation
“…MAPK15 is the most recently identified member of the MAPK family (16), and it is widely accepted to be upregulated in a variety of cancer types. Studies have shown that unlike other members of the MAPK family, the phosphorylation of MAPK15 is mainly self-phosphorylation, so its total protein level is positively correlated with the phosphorylation level (17,18). Additionally, the overexpression of MAPK15 promoted gastric cancer cell proliferation by stabilizing the expression of c-Jun (19).…”
Section: Metastasis-associated Gene Mapk15 Promotes the Migration Andmentioning
confidence: 99%
“…Accumulating evidences have shown that atypical MAPKs play critical roles in the development of tissues and participate in various diseases [8][9][10]. MAPK4, alias ERK4 or p63 MAPK, is the member of atypical MAPKs and closely related to MAPK6 with 73% amino acid identity in the kinase domain [11].…”
Section: Introductionmentioning
confidence: 99%